2007
DOI: 10.1007/s11242-007-9172-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pore Network in Three-dimensional (3D) Grain Bulks Using X-ray CT Images

Abstract: The knowledge of distribution of pore space inside grain bulks is essential for determining the airflow resistance of grains. In this study, the internal pore structure and the 3D-distribution of air paths inside grain bulks were studied using X-ray computed tomography images. Image analysis methods were applied to the binary 3D X-ray CT images on the spatial distribution of voids to generate the connected, individualized pore objects of different size and shapes. Morphometric parameters, such as 3D air path v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…With an increase in vertical pressure, the fractal dimension of the grain pile at the same location increased. Similar results were obtained by Neethirajan and Jayas (2007), who found that the complexity of the soybean pore shapes varies greatly along the horizontal direction. This study shows that the pressure effect does not reduce the complexity difference of the grain pile pore shapes.…”
Section: Simulated Porosity (L)supporting
confidence: 88%
“…With an increase in vertical pressure, the fractal dimension of the grain pile at the same location increased. Similar results were obtained by Neethirajan and Jayas (2007), who found that the complexity of the soybean pore shapes varies greatly along the horizontal direction. This study shows that the pressure effect does not reduce the complexity difference of the grain pile pore shapes.…”
Section: Simulated Porosity (L)supporting
confidence: 88%
“…3D images of real porous media can be obtained using serial sectioning (Adler et al 1990;Lymberopoulos and Payatakes 1992;Vogel and Roth 2001;Silin and Patzek 2006;Jiang et al 2007), which can give very high resolution in the plane of the slices but is destructive and less amenable to automation. Hence, the more popular approaches are non-destructive imaging techniques such as XCT (Petrovic et al 1982;Auzerais et al 1996;Al-Raoush and Willson 2005a,b;Ruffino et al 2005;Neethirajan and Jayas 2008), MRI (Baldwin et al 1996;Botto et al 1996;Kose 1996;Pauli et al 1997), and confocal microscopy (Mickel et al 2008). Resolution in these techniques typically ranges between 0.1 and 100 碌m, and the final data sets provide quantitative descriptions of the 3D pore structure.…”
Section: Network Modelingmentioning
confidence: 99%